2016
DOI: 10.1590/1807-3107bor-2016.vol30.0088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modeling liquid/resin and polishing on the color change of resin composite

Abstract: Modeling liquids/resins have been used to build up resin composite (RC) restorations, although there is a lack of information regarding their effects on the color stability of the latter. Therefore, the purpose of the present study was to evaluate the effects of the presence of modeling liquid between layers of RC and the finishing/polishing state of the material on color change in specimens exposed to red wine staining over time. Specimens were prepared by placing four increments (±0.5 mm thick) of RC (Filtek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 27 publications
1
44
0
10
Order By: Relevance
“…This finding is corroborated by recent studies. 3,5 Specimens prepared with SBMP appeared to be stronger and more cohesively packed than those prepared without, and these features could positively influence the chemophysical stability of the composite. 2,3 The absence of translucency changes for specimens stored in wine, with the only exception occurring in the SB group after 12 months of storage, is notable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is corroborated by recent studies. 3,5 Specimens prepared with SBMP appeared to be stronger and more cohesively packed than those prepared without, and these features could positively influence the chemophysical stability of the composite. 2,3 The absence of translucency changes for specimens stored in wine, with the only exception occurring in the SB group after 12 months of storage, is notable.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used the CIE L * a * b * system to evaluate ΔE * . Although some recent studies have demonstrated that another measurement system, i.e., CIEDE2000, may provide a better fit than the former in the evaluation of color difference thresholds, 10,18,19,20 many other studies use the CIE L*a*b* color system to analyze color outcomes in dentistry 3,5,21,22,23 because this system features predictability and clinical importance. ΔE * did not increase after 12 months of storage in specimens prepared with the modeling liquids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, obtaining satisfactory esthetic restorations depends on both clinicians’ skill and the physical properties of the composite, including its handling characteristics. As the stickiness of several composites can hinder the insertion and sculpting procedures, some clinicians have used low viscosity materials as modeler liquids to facilitate the building up of the restoration by reducing the surface tension of the composite . Moreover, the low viscosity resin might penetrate through any porosity created during the incremental insertion of the composite, helping to reduce the defects on the restoration's body and ultimately improving the mechanical properties and color stability …”
Section: Introductionmentioning
confidence: 99%
“…The surface morphology including roughness can be more exposed to color changes. Sedrez-Porto et al (26) reported that polishing is essential for color stability of resin composites. Only thermal cycling was used in this study.…”
Section: Study Limitationsmentioning
confidence: 99%